Interactions between bacterial surfaces and milk proteins, impact on food emulsions stability - Mai Huong Ly (2008)
Bacteria possess physicochemical surface properties such as hydrophobicity, Lewis acid/base and charge which are involved in physicochemical interactions between cells and interfaces. Moreover, food matrices are complex and heterogeneous media, with a microstructure depending on interactions between the components in media (van der Waals, electrostatic or structural forces, etc.). Despite the presence of bacteria in fermented products, few works have investigated how bacteria interact with other food components. The objective of the present study was to determine the effects of the surface properties of lactic acid bacteria on the stability of model food emulsions. The bacteria were added to oil/water emulsions stabilized by milk proteins (sodium caseinate, whey proteins concentrate or whey proteins isolate) at different pH (from 3 to 7.5). The effect of bacteria on the emulsions stability depended on the surface properties of strains and also on the characteristics of emulsions. Flocculation and aggregation phenomena were observed in emulsion at pHs for which the bacterial surface charge was opposed to the one of the proteins. The effects of bacteria on the stability of emulsion depended also on the concentration of cations present in media such as Ca2+. These results show that the bacteria through their surface properties could interact with other compounds in matrices, consequently affecting the stability of emulsions. The knowledge and choice of bacteria depending on their surface properties could be one of the important factors to control the stability of matrices such as fermentation media or fermented products.